Self-use of skin-bleaching products among women attending a family medicine clinic: A cross-sectional study - Zinab A Alatawi; Mohammed ALShahrani (Wolters Kluwer Medknow Publications, 2020)
Background: The use of skin-lightening creams is common and widespread in African, Asian, and North American colored no brown to dark. Use of skin-bleaching agents has been reported in Saudi Arabia. The long-term use of these products for several months to years may cause cutaneous or systemic side effects. Purpose: This study aimed to assess the prevalence of self-use of skin-bleaching agents among Saudi women as well as the level of awareness, attitudes, and practice toward the use of these agents. Methods: A cross-sectional study was conducted by the selection of systematic random sampling of female attending the Family Medicine Clinic at Prince Mansour Military Hospital. The data collected by a structured questionnaire included information about background variables and attitudes, awareness, and practice regarding the use of skin-bleaching agents. The data were analyzed using statistical software to yield descriptive and inferential statistics. Results: A total of 358 women aged between 18 and 55 years were included in this study. Nearly 25% of the women were current users of skin-bleaching agents, while 39.6% were only previous users. About a third of women used bleaching creams in the treatment of hypo or hyperpigmented skin and 29.4% used them for cosmetic purposes. Regarding the source of these agents, 38% of women obtained them by medical prescription and 27.8% were from pharmacy without prescription. The reason for using skin-bleaching creams varied: 51.6% of females used creams to increase beauty, 51% for making a new look, 6% for increasing self-confidence, and 4.3% to increase the stability of marriage. Almost 56% of the women reported that cortisone is the most dangerous component in the skin-bleaching agents. Nearly 33% of the women reported being willing to use a quick whitening agent from an unknown source. Higher education and higher income were associated with greater use of skin-lightening creams. Conclusion: The lifetime use of skin-bleaching agents was relatively high, divided evenly on cosmetic and curative purposes. The level of awareness about these agents is low because a considerable proportion of respondents agreed to use agents from unknown sources, in addition to the high use of skin-bleaching agents obtained without medical or pharmacist consultation.